MENGAPA MASIH TERJADI PENEMPATAN GURU YANG TIDAK SESUAI KEAHLIAN - Adam Damiri; Imam Khaudli (CV. Adiba Aisha Amira, 2025)
This study examines the main factors causing teacher placement mismatch with their field of expertise and formulates policy and technology-based solutions to overcome it. The purpose of this study is to identify the main causes of the problem, such as the imbalance in teacher distribution, recruitment and transfer policies that are not based on competency, and the lack of adaptation training programs for teachers who teach outside their fields. This study uses a mixed-method approach with data collection techniques in the form of surveys, big data analysis, in-depth interviews, and case studies of teachers and policy makers in the education sector. Data analysis was carried out using descriptive statistical techniques, logistic regression, and policy analysis. The results of the study show that the uneven distribution of teachers causes many teachers in remote areas to teach outside their fields, while in urban areas there is a surplus of teachers in certain subjects. In addition, recruitment and transfer policies that emphasize administrative aspects without considering teacher expertise worsen the mismatch in teaching. The lack of adaptation training programs for teachers who experience a mismatch in their teaching fields also has an impact on the quality of learning. Therefore, this study recommends an equal distribution of teachers based on the real needs of schools, improvements to competency-based transfer policies, and the provision of adaptive training programs for teachers to improve the overall quality of education.